2017
DOI: 10.1080/21645515.2017.1353845
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for cow's milk allergy

Abstract: Oral immunotherapy (OIT) is used regularly for young children with cow's milk (CM) allergy and has been shown to be effective in several studies. However, adverse events occur frequently during OIT. Furthermore, there are only 5 randomized controlled trial studies of CM-OIT and these are low-powered single center trials. Therefore, evidence levels are also low and sometimes frequent and severe allergic events occur during the OIT. Furthermore, there are no standardized protocols in pediatric allergy guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 69 publications
0
24
0
6
Order By: Relevance
“…5,6 Because a standard protocol in pediatric guidelines is non-existent, and due to the scarcity of randomized clinical trials with long-term follow-ups, an avoidance therapeutic approach is not widely used. 6 Moreover, the ability of OIT to induce long-term food tolerance and the adverse effects, especially gastroenteric complications, are yet to be established. 7,13 It has been reported that many children with milk allergy can better tolerate the modified allergens in baked milk products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Because a standard protocol in pediatric guidelines is non-existent, and due to the scarcity of randomized clinical trials with long-term follow-ups, an avoidance therapeutic approach is not widely used. 6 Moreover, the ability of OIT to induce long-term food tolerance and the adverse effects, especially gastroenteric complications, are yet to be established. 7,13 It has been reported that many children with milk allergy can better tolerate the modified allergens in baked milk products.…”
Section: Discussionmentioning
confidence: 99%
“…Milk allergy is one of the most common food allergies in young children, with a great impact on both children's and their caregivers’ lives . Research had always focused on therapies other than food avoidance for milk allergy such as oral desensitization . Because a standard protocol in pediatric guidelines is non‐existent, and due to the scarcity of randomized clinical trials with long‐term follow‐ups, an avoidance therapeutic approach is not widely used .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes oral (OIT), sublingual (SLIT), and epicutaneous (EPIT) immunotherapies (reviewed in), and single‐allergen OIT for peanut allergy has been submitted to the FDA for approval . OIT has also been studied for milk allergy in numerous clinical trials . However, most evidence suggests that OIT is not effective to induce tolerance or durable sustained unresponsiveness (SU) to food allergens.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini menunjukkan bahwa imunoterapi sublingual dapat secara efektif menimbulkan desensitisasi pada pasien alergi makanan dewasa, namun karena 54,5% subjek penelitian mengalami sindroma alergi oral, sulit untuk menerapkan hasil penelitian ini secara lebih luas pada pasien yang lain 26,27. Alergi Susu SapiPenelitian pendahuluan di Perancis mengujicobakan imunoterapi sublingual pada 8 orang subjek alergi susu sapi yang terkonfirmasi melalui DBPCFC dan pemeriksaan kadar IgE spesifik susu sapi 28,29. Dosis dimulai dengan 0,1 mL dan ditingkatkan sebesar 0,1 mL setiap 15 hari hingga tercapai dosis 1 mL perhari.…”
unclassified